2017
DOI: 10.1002/mma.4410
|View full text |Cite
|
Sign up to set email alerts
|

Stability and bifurcation in epidemic models describing the transmission of toxoplasmosis in human and cat populations

Abstract: A five-dimensional ordinary differential equation model describing the transmission of Toxoplamosis gondii disease between human and cat populations is studied in this paper. Self-diffusion modeling the spatial dynamics of the T. gondii disease is incorporated in the ordinary differential equation model. The normalized version of both models where the unknown functions are the proportions of the susceptible, infected, and controlled individuals in the total population are analyzed. The main results presented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Three papers focused on cat-human transmission ( Ferreira et al, 2017 ; González-Parra et al, 2009 ; Yongzhen et al, 2018 ). González-Parra et al (2009) developed a compartment model for exploring the dynamics of T. gondii transmission to humans (SIC-type: susceptible, infected, controlled (people in treatment)) with cat (SI-type: susceptible, infected) as a vector of transmission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three papers focused on cat-human transmission ( Ferreira et al, 2017 ; González-Parra et al, 2009 ; Yongzhen et al, 2018 ). González-Parra et al (2009) developed a compartment model for exploring the dynamics of T. gondii transmission to humans (SIC-type: susceptible, infected, controlled (people in treatment)) with cat (SI-type: susceptible, infected) as a vector of transmission.…”
Section: Resultsmentioning
confidence: 99%
“… Ferreira et al (2017) and Yongzhen et al (2018) extended the model of González-Parra et al (2009) to describe the transmission of T. gondii between cat and human populations. Both models assumed that horizontal transmission of the parasite to humans and cats was only through contact with infected cats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then they spread by all over epithelial cells and subsequently are expelled to the environment through the cat feces. Ferreira et al [11], studied the dynamical behaviours of both deterministic and spatial models of toxoplasmosis disease in cat and human populations. They showed that the deterministic model exhibits a trans-critical bifurcation and the system has no periodic orbits inside the positive octant.…”
Section: Introductionmentioning
confidence: 99%